Risk Analysis on Foreign Exchange Using Value-at-Risk Parametric Approach - Susanto, Sunarta; Riaman, Riaman; Sukono, Sukono (International Journal of Global Operations Research, 2022)
Foreign Exchange or usually known as Forex are one of the most famous investment objects. When investing in Forex, it is necessary to know the movements of the foreign exchange price as well as the risk that might happen. The purpose of this study is to predict the level of risk, seeing the characteristics of foreign exchange, and compare which foreign exchange is better to invest in. The Value-At-Risk (VaR) models used to predict the risk of the foreign exchange are VaR of standard normal distribution approach, VaR of Student-t distribution approach, and Modified VaR normal. Based on the research, the potential loss for AUD is Rp 9,445.26, CAD is Rp 7,972.62, CHF is Rp 7,073.74, EUR is Rp 6281.90, GBP is Rp 9,234.37, JPY is Rp 10,971.68, SGD is Rp 3,988.65, and USD is Rp 2,896.47 with an assumption that an investor invests as much as Rp 1,000,000.00 to each foreign exchange. USD is the best foreign exchange to choose because it has the lowest potential risk based on its VaR.